Adverse childhood experience and asthma onset: a systematic review - Daniel Exley; Alyson Norman; Michael Hyland (European Respiratory Review, 2015)
Adverse childhood experiences such as abuse and neglect are associated with subsequent immune dysregulation. Some studies show an association between adverse childhood experiences and asthma onset, although significant disparity in results exists in the published literature. We aimed to review available studies employing a prospective design that investigates associations between adverse childhood experience and asthma. A search protocol was developed and studies were drawn from four electronic journal databases. Studies were selected in accordance with pre-set inclusion criteria and relevant data were extracted. 12 studies, assessing data from a total of 31 524 individuals, were identified that investigate the impact of a range of adverse childhood experiences on the likelihood of developing asthma. Evidence suggests that chronic stress exposure and maternal distress in pregnancy operate synergistically with known triggers such as traffic-related air pollution to increase asthma risk. Chronic stress in early life is associated with an increased risk of asthma onset. There is evidence that adverse childhood experience increases the impact of traffic-related air pollution and inconsistent evidence that adverse childhood experience has an independent effect on asthma onset.